An ultrathin photosensitizer for simultaneous fluorescence imaging and photodynamic therapy. Issue 45 (21st May 2018) - Hu, Tongyang; He, Jun; Zhang, Shaomin; Mei, Xuan; Zhang, Weiku; Liang, Ruizheng; Wei, Min; Evans, David G.; Duan, Xue
Abstract : An ultrathin photosensitizer was prepared by immobilization of chlorin e6 (Ce6) and carbon dots (CDs) onto layered double hydroxide (LDH) nanosheets, which exhibited excellent fluorescence imaging and photodynamic therapy performance toward cancer theranostics. Abstract : An ultrathin photosensitizer was prepared by immobilization of chlorin e6 (Ce6) and carbon dots (CDs) onto layered double hydroxide (LDH) nanosheets, which exhibited excellent fluorescence imaging and photodynamic therapy performance toward cancer theranostics.